Physician-assisted suicide travel constraints: thematic content analysis of online reviews. Issue 4 (2nd October 2019) - Wen, Jun; Yu, Chung-En; Goh, Edmund
ABSTRACT: Constraints to participating in leisure activities have been studied extensively. Yet given the sensitive nature of death and death-related topics, little effort has been invested in understanding travel constraints that limit people's decisions to engage in physician-assisted suicide travel. As this form of travel is a relatively new area of interest in the tourism literature, this study investigates the public's perceptions of physician-assisted suicide travel by extracting online comments from user-generated content. By applying thematic content analysis with a deductive approach, a pre-coding scheme was developed based on the hierarchical constraint model. Four travel constraints were identified: perceived incapability and lack of personal support (intrapersonal constraints), lack of suitable travel agencies and services (structural constraint), and complex travel decision making. The latter consisted of two sub-dimensions: individualistic decisions (intrapersonal constraint) and collectivistic decisions (interpersonal constraint). The findings of this study help to contextualise physician-assisted suicide practices and knowledge in a tourism context. Relevant practical implications are also discussed.